2001
DOI: 10.1038/35053094
|View full text |Cite
|
Sign up to set email alerts
|

MAD2 haplo-insufficiency causes premature anaphase and chromosome instability in mammalian cells

Abstract: The mitotic checkpoint protein hsMad2 is required to arrest cells in mitosis when chromosomes are unattached to the mitotic spindle. The presence of a single, lagging chromosome is sufficient to activate the checkpoint, producing a delay at the metaphase-anaphase transition until the last spindle attachment is made. Complete loss of the mitotic checkpoint results in embryonic lethality owing to chromosome mis-segregation in various organisms. Whether partial loss of checkpoint control leads to more subtle rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
653
2
4

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 698 publications
(688 citation statements)
references
References 26 publications
29
653
2
4
Order By: Relevance
“…As these phenotypes were similar to those found for mutations in the mitotic checkpoint proteins Mad2 and BubR1 (Michel et al, 2001), it was conceivable that Wnt signal activation affected the checkpoint and/or subsequent apoptotic pathway. We focused our attention to Cdc2 (Cdk1), because it is one of the key mitotic progression regulators under the checkpoint, and reduction of its activity is required for exit from the mitotic phase (Tan et al, 2002).…”
Section: Es Cells With High Abi Produce New Chromosomal Aberrationssupporting
confidence: 65%
See 1 more Smart Citation
“…As these phenotypes were similar to those found for mutations in the mitotic checkpoint proteins Mad2 and BubR1 (Michel et al, 2001), it was conceivable that Wnt signal activation affected the checkpoint and/or subsequent apoptotic pathway. We focused our attention to Cdc2 (Cdk1), because it is one of the key mitotic progression regulators under the checkpoint, and reduction of its activity is required for exit from the mitotic phase (Tan et al, 2002).…”
Section: Es Cells With High Abi Produce New Chromosomal Aberrationssupporting
confidence: 65%
“…Enhanced cell survival and escape from G2/M arrest upon prolonged microtubule disruption in cells with Wnt signal activation It has been reported that CIN can be caused by dysregulation of the mitotic spindle checkpoint that ensures accurate chromosome segregation during M phase (Michel et al, 2001;Shin et al, 2003). In addition to G1 progression (van de Wetering et al, 2002), Wnt signaling has been reported to be involved also in G2/M progression (Sekiya et al, 2002).…”
Section: Es Cells With High Abi Produce New Chromosomal Aberrationsmentioning
confidence: 99%
“…Premature segregation of sister chromatids is often found in cells that are defective in the spindle assembly checkpoint, such as mitotic arrest deficient 2 (Mad2) (Michel et al, 2001) and Brca1 (Wang et al, 2004) mutant cells. The spindle assembly checkpoint plays an essential role in maintaining genome integrity by Aurora-A induces mammary tumor formation X Wang et al holding cells with unaligned chromosomes at metaphase (Amon, 1999;Yoon et al, 2002;Andreassen et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, FAT10 was found to interact with MAD2, a mitotic spindle checkpoint protein (Liu et al, 1999) that has been shown to be important for maintaining genome stability (Michel et al, 2001). Dysregulation of MAD2 has also been implicated in tumorigenesis (Michel et al, 2001;Wang et al, 2002;Li et al, 2003).…”
Section: Fat10 Is Negatively Regulated By P53mentioning
confidence: 99%
“…One of the G2/M genes that are downregulated by p53 is MAD1 (Chun and Jin, 2003). Both MAD1 (Luo et al, 2002) and FAT10 (Liu et al, 1999) are capable of interacting with MAD2, the spindle checkpoint protein whose dysregulation can lead to genomic instability and tumorigenesis (Michel et al, 2001;Hernando et al, 2004).…”
Section: Fat10 Is Negatively Regulated By P53mentioning
confidence: 99%